Comparison of estimated glomerular filtration rate equations in elderly with chronic kidney disease - Swaroopa Deme; Pardhu Bharath Neelam; Sateesh Killi; Sree Bhushan Raju; Y Satyanarayana Raju (Journal of Clinical and Scientific Research, 2021)
Background: Chronic kidney disease (CKD) a growing epidemic in India with limited studies addressing the problem of ideal equation for estimated glomerular filtration rate (eGFR) among elderly Indian patients. Currently, eGFR is calculated employing the CKD Epidemiology Collaboration (CKD-EPI) equations of which the combination of creatinine and cystatin-c (eGFR cr-cys) is recommended as more accurate. However, preferred equations and filtration markers in elderly individuals are debated. Methods: The present prospective observational study conducted from 2012 to 2014 at our tertiary care centre, aimed at identifying the best filtration marker and eGFR equation for elderly CKD patients. One hundred and seven elderly CKD patients were studied. Comparison of eGFR equations derived from modification of diet in renal disease (MDRD) and CKD-EPI, based on creatinine and cystatin-c was done. Results: Median creatinine was 2.4, and median cystatin-c was 1.9. On comparing the correlation between all four equations by spearman correlation coefficient, difference was noted. eGFR by EPI-creatinine and cystatin-c correlated with all other three equations with correlation coefficient of 0.84 for both MDRD, EPI-creatinine and 0.82 for EPI-cystatin-c equations, respectively. Conclusions: Of the four equations for eGFR, EPI-cystatin-c and creatinine equation showed better correlation with all other equations, hence might be the better equation for confirmation and classification of the elderly CKD patients.